2018
DOI: 10.1016/j.jamda.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Quality Hospice Care in Adult Family Homes: Barriers and Facilitators

Abstract: The adult family home setting can amplify both the benefits and challenges associated with receipt of hospice. When choosing an adult family home, older adults and their families should strongly consider selecting a home with a track record of positive collaborations with hospice agencies if the need for end-of-life care is anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Taken together, this gap in nurses’ responses to FCGs’ queries highlights the potential of educational interventions focusing on personalized-skilled communication in home hospice (e.g., education-coaching intervention, motivational interview skills, advanced validation skills) to better guide both hospice nurses and FCGs to deal with pain-related concerns. 24 A recent qualitative study 25 with 73 FCGs in home hospice identified that personalized-skilled communication (i.e., considering individual FCGs’ preferences in managing cancer-pain and communication styles) facilitated the provision of quality care in home hospice. Including FCGs in in-person or videoconference-based interdisciplinary team (IDT) meetings on a regular basis is also effective in improving access to hospice care providers, assessing FCGs’ barriers and discussing goals of care.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, this gap in nurses’ responses to FCGs’ queries highlights the potential of educational interventions focusing on personalized-skilled communication in home hospice (e.g., education-coaching intervention, motivational interview skills, advanced validation skills) to better guide both hospice nurses and FCGs to deal with pain-related concerns. 24 A recent qualitative study 25 with 73 FCGs in home hospice identified that personalized-skilled communication (i.e., considering individual FCGs’ preferences in managing cancer-pain and communication styles) facilitated the provision of quality care in home hospice. Including FCGs in in-person or videoconference-based interdisciplinary team (IDT) meetings on a regular basis is also effective in improving access to hospice care providers, assessing FCGs’ barriers and discussing goals of care.…”
Section: Discussionmentioning
confidence: 99%
“…45 However, AFHs differ from social model hospice RCHs in that the care provided by AFHs is not geared toward the provision of end-of-life care; they are managed by the department of social services; and they operate as fee for service and care may be covered by insurance including Medicaid. 46 While Medicaid-eligible patients may be more likely to reside in AFHs than RCHs, the RCH model is a valuable option for economically disadvantaged populations, given that room, board and care are provided free of charge.…”
Section: Discussionmentioning
confidence: 99%